Fetishistic lnternationalism: Jousting with unreality in Greece - Ifestos, Panayiotis (Études helléniques / Hellenic Studies, 1997)
This analysis is basically a study of political philosophy of international relations relating both to general trends and to the diplomacy of a small state, namely Greece. The author examines some fundamental aspects of current IR theory as regards evolving trends and structures at the international level. Referring to alternative approaches as they develop in the 1990s, the author concludes that, no credible alternative to the sovereignty/anarchy paradigm is provided. Turning to Greece, the author refers to representative views which show the academic and political discourse endorse, almost unquestionably, the most radical form of “neoliberal ideology”. The foreign policy of a small state, it is suggested, is either rational, in which case it has national interest as a supreme criterion and as a beacon for orientation, or it is irrational and counterproductive.